Stabilising Cobalt Sulphide Nanocapsules with Nitrogen-Doped Carbon for High-Performance Sodium-Ion Storage - Yilan Wu; Rohit R. Gaddam; Chao Zhang; Hao Lu; Chao Wang; Dmitri Golberg; Xiu Song Zhao (Nano-Micro Letters, 2020)
Abstract Conversion-type anode materials with a high charge storage capability generally suffer from large volume expansion, poor electron conductivity, and sluggish metal ion transport kinetics. The electrode material described in this paper, namely cobalt sulphide nanoparticles encapsulated in carbon cages (Co9S8@NC), can circumvent these problems. This electrode material exhibited a reversible sodium-ion storage capacity of 705 mAh g−1 at 100 mA g−1 with an extraordinary rate capability and good cycling stability. Mechanistic study using the in situ transmission electron microscope technique revealed that the volumetric expansion of the Co9S8 nanoparticles is buffered by the carbon cages, enabling a stable electrode–electrolyte interface. In addition, the carbon shell with high-content doped nitrogen significantly enhances the electron conductivity of the Co9S8@NC electrode material and provides doping-induced active sites to accommodate sodium ions. By integrating the Co9S8@NC as negative electrode with a cellulose-derived porous hard carbon/graphene oxide composite as positive electrode and 1 M NaPF6 in diglyme as the electrolyte, the sodium-ion capacitor full cell can achieve energy densities of 101.4 and 45.8 Wh kg−1 at power densities of 200 and 10,000 W kg−1, respectively.